Application of System Engineering in Election Voting System - Mudda, Mallikarjun; Bhargava Choubey, Shruti (International Journal of Engineering and Technology, 2018)
Election System is one of the indicators of the democratic country when this country is giving equal rights to the eligible citizens to choose their leaders or to give their candidatures, to participate in the country development by criticizing the government on how thing are being done and how they want to be done (i.e. means listen the views of the citizens). An E-voting system is one of the system engineering where different technologies are applied to analyze, design and implement a dynamic system which is satisfying the user needs. In this work we are discussing on the futures of Election Management System (EMS) by mentioning some of the problems and coming up with the solutions. The system is having the strong securities in the way that the hackers cannot be able to enter our system to make any change during the registration of the voters and candidates as well as in the election period till the end of election (i.e. tabulation, store votes, and display the final election results). We are developing, designing and implementing Electronic Voting Machine composed by Hardware, Software and Network.Â Â Â Â Â Â Â Â